A Redundant Recurrent Cerebellar Model Articulation Control System for Industrial Applications - Ta, V. P.; Dang, X. K. (Engineering, Technology & Applied Science Research, 2019)
Because of increasing reliability requirements of the applications in industrial areas, the control systems must guarantee the stability and robustness during operation and continuously maintain control and supervisory process. In order to meet the above requirements, this study proposes a redundant recurrent cerebellar model articulation control system (RRCMACS) for controlling industrial applications, in particular the water level and the pressure in a tank. Therein, the stability and the robustness of the applications are guaranteed by the recurrent cerebellar model articulation controller (RCMAC) and the redundant solution maintains continuously control and supervisory process. To adapt industrial applications, a Programmable Logic Controller (PLC) was used to build the control system and industrial networks were used to transfer data between the control system and field devices.